Impacto familiar del diagnóstico de muerte inminente (2013)
ABSTRACT: The article analyze the way facing the appearance of an advanced oncologic disease in one of its members, the family history and the relationship between family members favor or hinder the handling of the Information, the emotional expression, and the company provided to the ill person. Semistructures interviews were carried out to nine family groups and five patients; the information was interpreted using content analysis. The results suggested that families able to establish a truthful communication on the diagnosis and prognosis achieve mutual support links and greater role flexibility. Contrariwise, families with evident communication difficulties experience problems of interaction and in the process of accompanying their ill member.